ARTERIAL HYPERTENSION INFLUENCES THE HEALTH-RELATED QUALITY OF LIFE OF 65+ YEAR-OLD PATIENTS - Emilia K. Naseva; Konstantin N. Ramshev; Evelina M. Marinova; Nikola A. Ramshev; Vlayko E. Vodenicharov (Journal of IMAB)
This study aims to compare two health-related quality of life (HRQoL) measures of patients who reported having arterial hypertension (AH) and those who did not report this condition. Materials and methods: A population-based observational survey was performed in Sofia in 2017 through face-to-face interviews among 246 persons aged 65 and above. Two HRQoL instruments (SF-12 and WHO-5) and visual analogue scale (VAS) for self- perceived health were used. Results: The prevalence of AH was 67.1%. AH and non-AH patients were similar in age, gender, education, and marital status. VAS medians were significantly lower among AH patients (60 vs. 70, p = 0.012) as well as their SF-6D scores (78 vs. 82, p = 0.009). AH patients more often reported being limited in moderate activities (21.8% limited a lot vs. 7.4%, p= 0.018) as well as in climbing several flights of stairs (20.6% limited a lot vs. 11.1%, p = 0.001). They were also more affected by the pain (p= 0.026). This resulted in significantly lower scores in two SF-12 domains: Physical Functioning (p = 0.014) and Bodily Pain (p = 0.010). AH patients reported feeling active and vigorous less often (all the time 25.5% vs. 40.7%, p = 0.045). However, the total WHO-5 score did not differ significantly between groups (p > 0.05). Conclusion: In general, AH patients showed lower HRQoL compared to normotensive patients.